2015
DOI: 10.1063/1.4921095
|View full text |Cite
|
Sign up to set email alerts
|

X-ray beam compression by tapered waveguides

Abstract: We have fabricated linear tapered waveguide channels filled with air and imbedded in silicon for the hard x-ray regime, using a processing scheme involving e-beam lithography, reactive ion etching, and wafer bonding. Beam compression in such channels is demonstrated by coupling a pre-focused undulator beam into the channels, and recording the exit flux and far-field diffraction patterns. We achieved a compressed beam with a spot size of 16.48 nm (horizontal) × 14.6 nm (vertical) near the waveguide exit plane, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…33 Chen et al have observed that the transmission of tapered waveguides reduces to 0.96% from expected 8.9% due to the interfacial roughness and internal defects. 34 Prudnikov has shown that the field intensity inside the multilayer-based waveguide reduces by about 16% to 20% when rms roughness of all the layers is increased from 0 to 0.5 nm. 35 Thus, the lower densities of Ru layers and interfacial roughness of the sample deteriorate the field intensity inside the guiding layer.…”
Section: Determination Of Structural Parameters: Electric Field Intensity Calculationsmentioning
confidence: 99%
“…33 Chen et al have observed that the transmission of tapered waveguides reduces to 0.96% from expected 8.9% due to the interfacial roughness and internal defects. 34 Prudnikov has shown that the field intensity inside the multilayer-based waveguide reduces by about 16% to 20% when rms roughness of all the layers is increased from 0 to 0.5 nm. 35 Thus, the lower densities of Ru layers and interfacial roughness of the sample deteriorate the field intensity inside the guiding layer.…”
Section: Determination Of Structural Parameters: Electric Field Intensity Calculationsmentioning
confidence: 99%
“…Once the technical challenges for channel waveguides are solved, X-ray generation in waveguides beyond straight channels like tapered channels [CHS15], beamsplitters [HS16], split-and-delay lines or bent channels [Sal+15a] can provide entirely new possibilities for source designs. This toolbox of optics on a chip can be especially interesting for quantum optical experiments with hard X-rays at table-top instruments.…”
Section: Pulsed Laser-plasma Sources For X-ray Generation In Waveguidesmentioning
confidence: 99%